ANALISIS KUALITAS PELAYANAN PUBLIK DALAM MEMBERIKAN KEPUASAN KEPADA MASYARAKAT PADA PUSKESMAS LEMPAKE KOTA SAMARINDA - Salasiah dan Beni Azhar (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
In Law Number 36 Year 2009 explains that health is a healthy, physical, mental, spiritual and social condition that enables everyone to live productively socially and economically. And it has also been established that everyone is entitled to health care. Therefore, every element of society, individuals, families, are entitled to health services and the government is responsible for declaring, arranging to organize and supervise health care equally and reachable by the community.The purpose of this research is to know the level of quality of Puskesmas service in Lempake Kota Samarinda area. the research approach used is quantitative, the unit of analysis in this study are individuals. With descriptive qualitative methods with data collection techniques through questionnaires to patients and direct survey to obtain the necessary data about how the quality of health services in Puskesmas.The result of the research on the quality of health service of Puskesmas in Lempake area of Samarinda City is measured by using 5 dimensions of public service quality namely Tangible Evidence, Reliability, Responsiveness, Assurance and Empathy. The service performed by Puskesmas Lempake Kota Samarinda has been effective because it has received good appraisal by the society based on the five assessment indicators used, this is indicated by the recapitulation of five indicators of service quality is already above 60%, it shows that the quality of health services provided is good